Clinical Characteristic and Management of Central Serous Chorioretinopathy - Rio Rhendy; Andi Arus Victor (Majalah Oftalmologi Indonesia, 2016)
Background: Central serous chorioretinopathy (CSCR) is an abnormality in posterior segment of theeye, characterized by detachment of retinal neurosensory caused by localized accumulation of serousfluid. CSCR is commonly found in male (90%) with age ranging of 25 to 55 years old and oftenoccurs in white, Asia, and Hispanic. Subretinal fluid will be absorb spontaneously within 3-4 months,thus observation and risk factors modification are the initial management for CSCR for couple ofmonths. However, drugs use on CSCR can be considered to accelerate fluid resorption.Methods: This study is a descriptive-retrospective study, done in Vitreoretina Division of OphthalmologyDepartment, Cipto Mangunkusumo Hospital, Jakarta, from December 2015 to January 2016. Thesubjects were all CSCR patients, using medical records for data selection.Results: There were 90 patients with CSCR, but only 20 eyes from 19 patients could be included tothe study. Most of CSCR patients were male (84%), with age ranging from 25 to 55 years old, meanage of 40.31 years.Conclusion: Management of CSCR in Cipto Mangunkusumo Hospital gave significant improvementin UCVA and CMT.